Effects of Safranal on Tissue Oxidative Stress in Sub-Chronic Thinner-Addicted Rats - DÜZ, M.; FIDAN, A. F. (Journal of the Hellenic Veterinary Medical Society, 2020)
The present study was carried out to determine the effects of sub-chronic thinner addiction on the oxidant-antioxidant balance and oxidative stress on certain tissues and the possible protective effect of safranal against thinner toxication in rats. Adult male Wistar albino rats were randomly divided into four groups of 10 animals each as follows: control (C), safranal (S), thinner (T) and thinner+safranal (T+S). The control group received 1cc saline by gastric gavage. Safranal was administered to S and T+S groups by using gastric gavage at a dose of 100 mg/kg/day and volume of 0.1 mL/kg/day. Thinner inhalation was applied to T and T+S groups in a container with NaOH tablets twice a day. Levels of malondialdehyde (MDA), reduced glutathione (GSH), nitric oxide (NOx) metabolites, total antioxidant capacity (TAS) and total oxidant capacity (TOS) were determined in liver, lung, brain, kidney and testis tissues of the rats. In the T+S group, it was observed that the MDA levels significantly decreased in all tissues, except the kidney, in comparison to the thinner inhalation group (p = 0.000). When the NOx levels of the T+S group were compared with the levels of the T group, it was concluded that there existed a statistically significant decrease in the NOx levels in alltissues (p = 0.000). In T+S group, it was observed that safranal either eliminated or mitigated oxidative stress that developed in tissues through decreasing MDA and TOS levels and increasing GSH and TAS levels and caused significant decreases in NOX levels in all tissues. As a result, it was determined that safranal, although not uniform for all tissue types, had a protective potential against the damaging effects of oxidative stress caused by sub-chronic thinner inhalation.